2019
DOI: 10.3390/w11112205
|View full text |Cite
|
Sign up to set email alerts
|

A Rainwater Harvesting Accounting Tool for Water Supply Availability in Colorado

Abstract: Rainwater harvesting (RWH) is a renewable water supply option for nonpotable use, most commonly used for landscaping irrigation. Water rights in Colorado prohibit all RWH except residential rain barrels and a pilot project program that allows centralized rainwater harvesting for new development. Development of a natural catchment creates impervious surfaces, thereby increasing runoff, with a subsequent decrease in infiltration and losses to evapotranspiration; pilot projects are allowed to harvest a volume equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Most studies tried to improve groundwater use efficiency using smart solutions (Fornarelli et al, 2022). The remaining 15 studies considered other ecosystems, such as wetlands (Mahdianpari et al, 2021), lakes (Maleki et al, 2022), mountains (Gilliom et al, 2019), and rivers (Kartakis et al, 2017).…”
Section: Water-related Ecosystems (T6)mentioning
confidence: 99%
“…Most studies tried to improve groundwater use efficiency using smart solutions (Fornarelli et al, 2022). The remaining 15 studies considered other ecosystems, such as wetlands (Mahdianpari et al, 2021), lakes (Maleki et al, 2022), mountains (Gilliom et al, 2019), and rivers (Kartakis et al, 2017).…”
Section: Water-related Ecosystems (T6)mentioning
confidence: 99%
“…There is no green infrastructure requirement, although municipalities have strategies related to green infrastructure (City and County of Denver 2018). The City and County of Denver have drainage criteria that two-year storms (residential) to five-year storms (commercial and industrial) should be fully conveyed within pipes and dedicated drainage channels, but not all sewersheds are meeting these criteria (Gilliom et al 2019). Stormwater improvements in the City and County of Denver to meet these criteria are expected to cost $1.48 billion (The City and County of Denver Storm Drinage Master Plan 2014).…”
Section: Case Study Background: Cleveland and Denvermentioning
confidence: 99%
“…Because of these restrictions, a tool to calculate the daily allowable harvest was developed using soil parameters and precipitation data. Using simulations from 2010 to 2017 from the Colorado Front Range, researchers concluded that rainwater harvesting can supply up to 50 percent of the annual demand for traditional landscaping irrigation water (Gilliom, Bell, Hogue, & McCray, 2019). Another study looked at simulations of rainwater harvesting and the capability of short-term rainfall data to produce accurate long-term predictions (Soares Geraldi & Enedir, 2019).…”
Section: Water Quantity and Floodingmentioning
confidence: 99%